Chemical transfer of warning information in non-injured fish - Jordao, L. C.; Volpato, G. L. (Brill Academic Publishers, 2000)
In this study we describe pacus, Piaractus mesopotamicus, detecting the presence of a predator by conspecific alerting pheromone. Moreover, we investigate whether this chemical information indicates the presence of a specific predator, or whether it indicates general disturbance. We exposed groups of pacus to the view of a predator fish (trahira, Hoplias malabaricus), a non-predator fish (piracanjuba, Brycon orbignyanus) or an aquarium without any fish (control), and then we transferred their water to isolated conspecifics. We set up six trials of each condition in which we analysed the dispersion and the distance from the visual stimulus in water-donor fish and the distance from the chemical stimulus in water-receiver pacus. This study showed that pacus visually identified the presence of another fish and recognised it as predator or non-predator. This is interpreted as an innate response. Such heterospecific detection affects the behaviour of pacus, which release chemicals that induce conspecifics to adopt a similar behavioural response. At least two chemicals might be involved, one of them possibly an alerting pheromone.
Keywords: chemical communication; disturbance pheromone; alerting pheromone; predator; fish behaviour; pacu; Piaractus mesopotamicus